TINJAUAN YURIDIS PEMBERATAN SANKSI TERHADAP APARAT PENEGAK HUKUM YANG MELAKUKAN TINDAK PIDANA KORUPSI - Andhika, Muhammad Zakhri; Erdianto, Erdianto; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Corruptions in Indonesia have been very widespread, and have even beenconsidered normal. Various efforts have been made by the state to eradicate thiscorruption, although it is still far from perfect. Law enforcement officials are noexception, which are institutions or institutions whose job is to implement the law,maintain security and order, and protect the rights and interests of the community,instead committing acts of corruption. This can cause problems from various aspects,and also to our country, which is a rule of law country. Not a few people view that thedecision on criminal sanctions for corruption is considered too light as well as casesof criminal acts of corruption by law enforcement officials.The type of research is normative research using literature studies in datasearch. This research is descriptive by using the method of synchronizing existingrules. In this study using qualitative methods in analyzing the data that has beencollected. The data used is secondary data in the form of codified rules.The results of this study explain how judges consider in deciding cases ofcorruption committed by law enforcement officials, which are considered unfair ingiving decisions, and the importance of increasing criminal sanctions against this.Because a law enforcement official is someone who really understands the law bothin theory and in practice. In this case, the additional of sanctions against lawenforcement officials can be an appropriate preventive solution so that no more lawenforcement officers commit acts of corruption.Keyword : Corruption, Law Officer, Penal Addition